THE EFFECT OF PROFITABILITY AND LEVERAGE ON TAX AVOIDANCE WITH MODERATION OF CORPORATE GOVERNANCE IN MANUFACTURING COMPANIES IN THE FOOD & BEVERAGE SUB-SECTOR ON THE IDX - Rahmat Salim Fauzi P; Aminah Aminah (PT. Saha Kreasi Indonesia, 2026)
This study aims to examine the effect of profitability and leverage on tax avoidance and to analyze the moderating role of Corporate Governance in manufacturing companies in the Food & Beverage subsector listed on the Indonesia Stock Exchange (IDX) during 2022–2025. This study employs a quantitative approach using secondary data obtained from annual financial statements and corporate governance reports. The sample was selected using purposive sampling, resulting in 16 companies and 64 firm-year observations. Tax avoidance is measured using the Effective Tax Rate (ETR), profitability is measured by Return on Assets (ROA), leverage is measured by the Debt to Equity Ratio (DER), and Corporate Governance is proxied by the proportion of independent commissioners. The data were analyzed using panel data regression with the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA). The results show that profitability has a negative and significant effect on ETR (β = −0.2154; p = 0.0198), indicating that higher profitability is associated with higher tax avoidance. Leverage also has a negative and significant effect on ETR (β = −0.0318; p = 0.0437), indicating that higher leverage is associated with higher tax avoidance. Corporate Governance significantly moderates the relationship between profitability and tax avoidance, as indicated by the positive and significant ROA × KI interaction coefficient (β = 0.4128; p = 0.0318), suggesting that Corporate Governance weakens the tendency of highly profitable companies to engage in tax avoidance. In contrast, the DER × KI interaction is positive but statistically insignificant (β = 0.0524; p = 0.1837), indicating that Corporate Governance does not significantly moderate the relationship between leverage and tax avoidance. The regression model has an R-squared value of 0.5782, indicating that 57.82% of the variation in ETR is explained by the variables included in the model. These findings support Agency Theory and highlight the importance of effective Corporate Governance in controlling corporate tax avoidance, particularly among highly profitable companies.